An Alternative History of the Arctic: The Origins of Ethnographic Filmmaking, the Fifth Thule Expedition, and Indigenous Cinema. Issue 1 (4th July 2020) - MacKenzie, Scott; Stenport, Anna Westerstahl
Abstract : The Fifth Thule Expedition (1921–24) generated extensive international attention through publications such as Knud Rasmussen's best seller, Across Arctic America (1927). It also appropriated thousands of Indigenous artifacts, shipped mostly to the National Museum of Denmark. The collection includes a little‐known film, Med Hundeslæde gennem Alaska ( With Dog Sled Through Alaska, 1927) shot in 1923–24 by Danish filmmaker and photographer Leo Hansen, in close collaboration with Rasmussen. The extant film materials reflect Rasmussen's status as an embedded ethnographic explorer because of his Greenlandic heritage and Indigenous language capacity. Through archival research, this article examines early Arctic cinema and early twentieth‐century representation of Inuit cultures.